Peran Kualitas Pelayanan Fiskus dalam Memoderasi Pengaruh Efektifitas Penerapan E-Filing, Pengetahuan Pajak dan Sanksi Perpajakan Terhadap Kepatuhan Wajib Pajak - Al Amin, Moch Hafidz Hamzah; Afifudin, Afifudin; Nandiroh, Umi (e_Jurnal Ilmiah Riset Akuntansi, 2024)
This study aims to analyze the moderating effect of quality of tax authorities service in the influence of use of e-filing, tax knowledge, tax sanction, on the firm value of KPP Pratama Singosari. The incidental sampling technique was used in this study. This type of research uses descriptive research methods through a quantitative approach. The quantitative approach method is a type of research that involves collecting data to test hypotheses or answer questions about an issue or topic, with moderated regression analysis processed using SmartPls version 4. The data sources used are primary data obtained from questionnaires and distributed directly to individual taxpayers registered at KPP Pratama Singosari. The research sample consisted of 170 respondents and was measured using a Likert scale. The use of e-filing does not affect taxpayer compliance at KPP Pratama Singosari, while tax knowledge, and tax sanctions significantly affects taxpayer compliance at KPP Pratama Singosari. The quality of taxpayer services also has a significant effect on taxpayer compliance. However, the quality of tax authorities' services does not moderate the relationship between the use of e-filing and tax knowledge with taxpayer compliance. Conversely, the quality of tax authorities' services can moderate the relationship between tax sanctions and taxpayer compliance.Keywords: Use of e-filling, tax knowledge, tax sanctions, quality of tax authorities services, and taxpayer compliance, KPP Pratama Singosari.